2020
DOI: 10.1007/s42729-020-00282-2
|View full text |Cite
|
Sign up to set email alerts
|

Response of the Organic Carbon Fractions and Stability of Soil to Alpine Marsh Degradation in Zoige, East Qinghai-Tibet Plateau

Abstract: Soil organic carbon (SOC) fractions play a crucial role in the carbon cycle of alpine wetland ecosystems and regional climate regulation. In the last decades, alpine marshes at Tibetan Plateau have undergone increased degradation. The effects of marsh degradation on soil labile and recalcitrant organic carbon fractions and on SOC stability remain unclear. In this study, we investigated changes in SOC fractions with different biochemical recalcitrance and stability in the marsh ecosystems with various levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Additionally, the loss of C pools owing to marsh degradation may also result in the release of moderate labile inorganic P from organic matter (Zhang et al, 2015). In this study, an increase in organic acids associated with a mobilization of phosphate-dissolving bacteria and a loss of organic C (Almeida et al, 2020;Gatiboni et al, 2021;Pu et al, 2020;Susilowati et al, 2019) can improve the activation from soil Ca 10 -P to organic P, non-occluded P and Ca 2 -P under marsh degradation, which was related to aerobic conditions and/or dense plant communities in degraded marshes. Therefore, the transformation from Ca 10 -P to Ca 2 -P via organic P and the nonoccluded P path was an important regulatory mechanism of P availability in soils during marsh degradation on the Zoige Plateau.…”
Section: Regulation Of Soil Phosphorus Forms On Available Phosphorus ...mentioning
confidence: 69%
See 1 more Smart Citation
“…Additionally, the loss of C pools owing to marsh degradation may also result in the release of moderate labile inorganic P from organic matter (Zhang et al, 2015). In this study, an increase in organic acids associated with a mobilization of phosphate-dissolving bacteria and a loss of organic C (Almeida et al, 2020;Gatiboni et al, 2021;Pu et al, 2020;Susilowati et al, 2019) can improve the activation from soil Ca 10 -P to organic P, non-occluded P and Ca 2 -P under marsh degradation, which was related to aerobic conditions and/or dense plant communities in degraded marshes. Therefore, the transformation from Ca 10 -P to Ca 2 -P via organic P and the nonoccluded P path was an important regulatory mechanism of P availability in soils during marsh degradation on the Zoige Plateau.…”
Section: Regulation Of Soil Phosphorus Forms On Available Phosphorus ...mentioning
confidence: 69%
“…Marsh wetlands on the Zoige Plateau with alpine and fragile environments are located on the eastern edge of the Qinghai‐Tibet Plateau, China, and have undergone degradation to different degrees because of climate changes and anthropogenic activities over the past 60 years (Shen et al, 2019). During the degradation process of marshes, the capacity of soil C sink decreased continuously (Ma et al, 2016; Pu et al, 2020; Zhou et al, 2020), which would likely accelerate wetland degradation and affect the processes of the P cycle, leading to a weakening of wetland ecological service functions, such as regulating climate, biodiversity maintenance and water conservation (Hambäck et al, 2022; Sun et al, 2023). More importantly, there exists a close coupling relationship among C, N and P elements (Luo et al, 2021; Newman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the loss of carbon pools owing to marsh degradation may also result in the release of moderate labile inorganic P such as Fe-P and Al-P from organic matter (Yuan et al, 2015;Zhang et al, 2015). In this study, an increase in organic acids associated with a mobilisation of phosphate-dissolving bacteria and a loss of organic carbon (Gatiboni et al, 2021, Almeida et al, 2020Susilowati et al, 2019;Pu et al, 2020) can improve the activation from soil Ca 10 -P to organic P, non-occluded P and Ca 2 -P under marsh degradation. Therefore, the transformation from Ca 10 -P to organic P was an important regulation mechanism of P availability in soils during marsh degradation on the Zoige plateau.…”
Section: Regulation Of Soil Phosphorus Forms On Available Phosphorus ...mentioning
confidence: 74%
“…Marsh wetlands on the Zoige Plateau with alpine and fragile environments are located on the eastern edge of the Qinghai-Tibet Plateau, China, and have undergone degradation to different degrees because of natural threats and human activities over the past 60 years (Li et al, , 2019Shen et al, 2019). Several studies have revealed that alpine marsh degradation has decreased soil C sink function by increasing C emission fluxes in the Zoige Plateau (Ma et al, 2016;Pu et al, 2020;Zhou et al, 2020). Furthermore, total P and available P significantly affect the concentration of organic C in the Zoige peatland soils (Luo et al, 2021).…”
mentioning
confidence: 99%
“…Traditional soil texture measurement methods rely on field soil sampling and laboratory chemical analysis, which are time-consuming, laborious, and costly, making it difficult to conduct large scale and multifrequency soil texture content monitoring 6 , 7 . In recent years, rapidly developing vision-near-infrared hyperspectral technology has been widely used in soil texture content estimation to address the contradiction between the demand for big data of soil texture and high cost 8 .…”
Section: Introductionmentioning
confidence: 99%